Histochemical, biochemical and ultrastructural assessment on mitochondrial functions in patients with non-syndromic cleft lip - Noor, Rabiatul Adawiyah Mohamad (2024)
Non-syndromic cleft lip/ palate (NSCL/P) is one of the congenital malformations that affects upper lip and/ or palate of an infant. Despite intensive research, the underlying factors of this craniofacial deformity are still vague. It is believed that oral clefts have a complex aetiology including genetic and environmental factors. The pathogenesis of clefts occurs during the embryonic phase, hence, the role of mitochondria in regulating cells during this phase is crucial. Inconsistent findings have been discovered by previous studies, therefore, the association of mitochondrial metabolic defects with cleft pathogenesis remains vague. Therefore, we aim to discover the role of mitochondria in cleft tissues of our population to obtain extensive findings. In this study, the objective is to explore the histological alteration of orbicularis oris muscle and the role of mitochondria in terms of their structure and activity in causing cleft lip formation. Cleft lip tissues were obtained from consented patients with non-syndromic cleft lip, whereas control normal tissues were obtained from consented patients who were unaffected by cleft lip. A normal human primary gingival fibroblast was used as a control for the assay. Forty cleft lip tissues and seven controls were obtained and processed according to the respective analysis: haematoxylin and eosin (H&E), modified Gomori trichrome, cytochrome c-oxidase (COX), adenosine triphosphatase (ATP-ase), transmission electron microscopy (TEM), and adenosine triphosphate (ATP) assay. Histological and histochemical findings were analysed using a light microscope and imaging cellSens software, ultrastructural findings were examined using JEOL JEM2100F Field Emission TEM, and a statistical analysis of ATP assay was analysed using independent samples t-test. A few skin conditions, such as inflammation in the epidermal layer and Fordyce spot formation, were noted in the cleft lip tissues. The presence of the pathological hallmark of mitochondrial myopathy, which is ragged red fibers, and the presence of novel COX-negative fibers were observed in the tissues of cleft lip. Also, light microscopy revealed fibrotic and disorganised fibers, including a high percentage of type II fibers. A minimal accumulation of mitochondria and lipid droplets in the fibers were detected by electron microscopy. By means of biochemical assessment, ATP concentrations were significantly lower in cleft tissues compared to the control (P = 0.0344). The report on the series of mitochondrial myopathic features in patients with non-syndromic cleft lip provides more evidence and further supports the hypothesis that a metabolic defect at the mitochondrial level occurs in non-syndromic cleft lip.